The impact of sensory neuropathy and inflammation on epithelial wound healing in diabetic corneas. (July 2022) - Yu, Fu-shin X.; Lee, Patrick S.Y.; Yang, Lingling; Gao, Nan; Zhang, Yangyang; Ljubimov, Alexander V.; Yang, Ellen; Zhou, Qingjun; Xie, Lixin
Abstract: Diabetic peripheral neuropathy (DPN) is the most common complication of diabetes, with several underlying pathophysiological mechanisms, some of which are still uncertain. The cornea is an avascular tissue and sensitive to hyperglycemia, resulting in several diabetic corneal complications including delayed epithelial wound healing, recurrent erosions, neuropathy, loss of sensitivity, and tear film changes. The manifestation of DPN in the cornea is referred to as diabetic neurotrophic keratopathy (DNK). Recent studies have revealed that disturbed epithelial-neural-immune cell interactions are a major cause of DNK. The epithelium is supplied by a dense network of sensory nerve endings and dendritic cell processes, and it secretes growth/neurotrophic factors and cytokines to nourish these neighboring cells. In turn, sensory nerve endings release neuropeptides to suppress inflammation and promote epithelial wound healing, while resident immune cells provide neurotrophic and growth factors to support neuronal and epithelial cells, respectively. Diabetes greatly perturbs these interdependencies, resulting in suppressed epithelial proliferation, sensory neuropathy, and a decreased density of dendritic cells. Clinically, this results in a markedly delayed wound healing and impaired sensory nerve regeneration in response to insult and injury. Current treatments for DPN and DNK largely focus on managing the severe complications of the disease. Cell-based therapies hold promise for providing more effective treatment for diabetic keratopathy and corneal ulcers. Highlights: Corneal epithelium, nerves, and resident immune cells form a functional "epineuroimmune" unit to maintain tissue homeostasis. Diabetes causes corneal epithelial abnormalities, including delayed wound healing and persistent epithelial defects. Diabetic corneal neuropathy and decreased neuropeptide secretion disturb epineuroimmune function and delay wound healing. Diabetic corneas have fewer resident immune cells and increased infiltration/inflammation in response to epithelialwounding. Immune and stem cell-based therapies hold promise as novel avenues for treating diabetic neurotrophic keratopathy.